Einige Bemerkungen zur Semantik der Sprechhandlung DANKEN im Schwedischen, Polnischen, Deutschen und anderen Sprachen - Zborowski, Piotr (Folia Scandinavica Posnaniensia, 2007)
The aim of the article is to analyse the most important semantic units of the act of thanking in Swedish, Polish and German. According to the etymology of the verbs tacka, dziękować and danken, the act of thanking may be paraphrased as ‘the speaker’s good thoughts towards the addressee’ (mental paraphrase). On the other hand, the etymology of thanking in the Romance languages allows the paraphrase in terms of a mercantile exchange: ‘giving something in return for something else’. These two paraphrases, though seemingly competing, do not exclude but rather complement each other: ‘good thoughts’ about someone can at the same time be interpreted as ‘giving them good thoughts for something good’.